Online Lead Generation: An Emerging Industry - Simon Stolz; Kilian C. Wisskirchen; Christian Schlereth; Alexander Hoffmann (Marketing Review St.Gallen, 2021)
In the emerging business of online lead generation, many conversational touchpoints have moved to the online space. These companies capture leads, sell them to partners, and often generate millions of revenue in the process. We abstract this novel digital business model in a framework, derive best practices and provide managerial recommendations.
Keywords: 650